INTERFERENSI BAHASA MELAYU MALAYSIA DALAM BERBAHASA INDONESIA MANTAN TKI DI DUSUN TANAH EJA KABUPATEN BULUKUMBA : MALAYSIAN MALAY LANGUAGE INTERFERENCE IN THE INDONESIAN LANGUAGE OF FORMER MIGRANT WORKERS IN TANAH EJA HAMLET, BULUKUMBA DISTRICT - Angga Pratama, Fikar; Azis; Fitri, Sakinah (Journal of Applied Linguistics and Literature, 2024)
This study aims to: (1) describe the phonological interference form of speech of former migrant workers in Tanah Eja Hamlet, Bulukumba Regency; and (2) describe the form of semantic interference of former migrant workers' speech in Tanah Eja hamlet, Bulukumba Regency. This type of research is qualitative research. This research was conducted in Tanah Eja hamlet, Bulukumba Regency, South Sulawesi. The focus of this research and the limitations of this research include tuturain kaita that experience interference, then studied in the semaintic category that is only related to lexical meaning. As for the phonological category, three types of phonological interference will be focused, namely phonological interference, phoneme changes, phoneme addition, and phoneme reduction / removal interference. The source of this research data was obtained by dairi haisil waiwaincairai laingsung maintain TKI in Tainaih Ejai Kaibupaiten Bulukumba hamlet. Data collection techniques through interview techniques, voice recording techniques, listening techniques and recording techniques. The research instrument consists of the main instrument is the researcher himself and supporting instruments include voice recorders, respondent biodata questionnaires, and interference data tables.The results revealed that from the results of direct interview research 15 respondents contained a total of 35 words phonological interference. The most abundant and frequent data is the category of changes in vowel phonemes in the middle of words. In addition, respondents were shown to experience semantic interference by obtaining 15 forms of conversation and 28 types of words that experienced interference, this conversation was quoted during structured and semi-structured interviews of former migrant workers in Tanah Eja hamlet.